Health economics evidence for food system policy: a systematic review of reviews - Fu, Lin; Pokhilenko, Irina; van Rens, Thijs; Smith, Richard; Frew, Emma (Frontiers in Nutrition, 2025)
Food system interventions are needed for improving public health and to address health inequalities. Economics evidence enables an understanding of the costs associated with these interventions when offset against the gains to society. Here, we define economic analysis as studies of the effect of an intervention on prices, profits or balance sheets. By mapping this evidence, we gain an understanding of whether interventions target the production (supply-side) or consumption (demand-side) aspects of the system. This is helpful for identifying which “cluster” of policies have been more readily investigated in the academic literature, what the evidence says, and where there are gaps in evidence. The aims of this review were to synthesise the economics evidence on food system interventions designed to improve population health, to identify the most studied areas of the system, the economics methods used, and any trends in methodological choices based on the type of intervention. A search strategy to identify reviews published between 2012 and 2024 was applied to seven databases. The focus was on the whole population in high-income countries. Thirty-six reviews were identified covering 718 primary studies. There were 21 reviews focused on demand-side interventions, such as taxes and subsidies on sugar-sweetened beverages or foods high in salt, sugar and fat, and only four reviews that looked at solely supply-side interventions. Eleven reviews were on a mix of both demand and supply side interventions. We found that supply side (e.g., reformulation) interventions were more effective at altering dietary behaviours when compared to demand side interventions (e.g., labelling). Supply-side evaluations tended to use ex-ante methods for hypothetical interventions, while demand side evaluations used a mix of both ex-ante and ex-post designs. Synthesising the cost-effectiveness of the interventions across the reviews was challenging due to heterogeneity of methods applied. Due to the wide range of agents and sectors involved, a cost–benefit analysis from a societal perspective is the most recommended economic evaluation method. Further studies are needed to identify the most efficient mix of intervention components likely to achieve substantial health and economic impacts.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, Identifier CRD42022360714.